The Psychological Characteristics of Developing Healthy Thinking In Students - Utkurovna , Atakhanova Sayyora (Indonesian Journal Publisher, 2024)
This article explores the challenges related to the harmonious development of students' independent and healthy thinking. It emphasizes the importance of fostering independence in decision-making and responsibility, as well as the formation of personal ideas and thoughts. The article also highlights the psychological aspects involved in cultivating healthy thinking among students.